2017
DOI: 10.3892/or.2017.5648
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbitacin B induces autophagy and apoptosis by suppressing CIP2A/PP2A/mTORC1 signaling axis in human cisplatin resistant gastric cancer cells

Abstract: Cancerous inhibitor of protein phosphatase 2A (CIP2A) is a human oncoprotein that is overexpressed in multiple kinds of tumors including gastric cancer (GC). Mammalian target of rapamycin complex 1 (mTORC1) over-activation is detected in GC and many other cancers. Previous study found that CIP2A/mTORC1 controls cell growth and autophagy through direct association. CIP2A plays an 'oncogenic nexus' in several cancer types to participate in the tumorigenic transformation and chemoresistance. In the present study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 41 publications
2
22
0
Order By: Relevance
“…The anticancer properties of CuB have drawn the attention of many researchers in recent years. We previously reported that CuB might target CIP2A and markedly reverse adriamycin and cisplatin resistance in breast and gastric cancer . In the present study, we report for the first time that CuB exhibits moderate anti‐GBM activity in vitro and in vivo, and enhances the efficacy of DDP, but does not show toxicity toward nude mice, demonstrating its therapeutic potential.…”
Section: Discussionsupporting
confidence: 59%
“…The anticancer properties of CuB have drawn the attention of many researchers in recent years. We previously reported that CuB might target CIP2A and markedly reverse adriamycin and cisplatin resistance in breast and gastric cancer . In the present study, we report for the first time that CuB exhibits moderate anti‐GBM activity in vitro and in vivo, and enhances the efficacy of DDP, but does not show toxicity toward nude mice, demonstrating its therapeutic potential.…”
Section: Discussionsupporting
confidence: 59%
“…The results implied that NUSAP1 expression was positively associated with the mTORC1 signalling pathway in GC specimens (Figure A). Previous studies reported mTORC1 signalling pathway was involved in modulating cell cycle, apoptosis, growth, EMT, migration, and invasion in various cancers . To verify the GSEA results, western blot was used to evaluate mTORC1 related effectors (mTOR, P70S6K, and S6).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies reported mTORC1 signalling pathway had influences on cell cycle progression and apoptosis. For instance, Liu et al revealed that cucurbitacin B could induce cell apoptosis via inhibiting CIP2A/PP2A/mTORC1 signalling axis in GC. The study of Wang et al indicated that metformin contributed to G0/G1 phase cell cycle arrest through targeting the AMPK/mTOR pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Topical application of CuB resulted in significant reduction of epidermal hyperplasia and inflammatory cytokines, and ameliorated psoriatic symptoms (Li et al, 2015). Natural cucurbitacins and their derivatives have been recognized as promising antitumor compounds for several types of cancer, including Non-small cell lung cancer (Marostica et al, 2017), Osteosarcoma (Zhang et al, 2017) and gastric cancer (Liu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%